Impact of manganese ferrite (MnFe2O4) nanoparticles on growth and magnetic character of barley (Hordeum vulgare L.). (December 2018) - Tombuloglu, Huseyin; Tombuloglu, Guzin; Slimani, Yassine; Ercan, Ismail; Sozeri, Hüseyin; Baykal, Abdulhadi
Abstract: The main objective of this study was to assess the uptake and translocation of MnFe2 O4 magnetic nanoparticles (MNPs) in hydroponically grown barley ( Hordeum vulgare L.). Hydrothermally synthesized and well characterized MNPs (average crystallite size of 14.5 ± 0.5 nm) with varied doses (62.5, 125, 250, 500, and 1000 mg L −1 ) were subjected to the plants at germination and early growing stages (three weeks). The tissues analyzed by vibrating-sample magnetometer (VSM) and transmission electron microscopy (TEM) revealed the uptake and translocation of MNPs, as well as their internalization in the leaf cells. Also, elemental analysis proved that manganese (Mn) and iron (Fe) contents were ∼7–9 times and ∼4–7 times higher in the leaves of MNPs-treated plants than the ones for non-treated control, respectively. 250 mg L −1 of MNPs significantly (at least p < 0.05) promoted the fresh weight (FW, %10.25). However, higher concentrations (500 and 1000 mg L −1 ) remarkably reduced the increase to %8 and %5, respectively, possibly due to the restricted water uptake. Also, catalase activity was increased from 91 (μM H2 O2 min −1 mg −1 ) to 138 in leaves, and decreased to 66 in roots upon 1000 mg L −1 of MNPs application. Chlorophyll and carotenoid contents were not significantly changed, except chlorophyll a (%6 increase at 1000 mg L −1, p < 0.05). Overall, MnFe2 O4 NPs were up-taken from the roots and migrated to the leaves which promoted the growth parameters of barley. Hence, MNPs can be suggested for barley breeding programs and can be proposed as effective delivery system for agrochemicals. However, the possible negative effect of MNPs due to its potential horizontal transfer from plants to animals via the food chain must be also considered. Graphical abstract: Image 1 Highlights: Nanoparticle's usage is getting to increase in the last decade. MNPs (14 nm in diameter) is uptaken by roots and translocated to leaves. Synthesized MNPs promoted growth of barley at lower dose. Also, MNPs affected the magnetic nature of plant.